Implications of the STAT5B and C1QBP Genes of Grain Aphid Sitobion avenae in the Transmission of Barley Yellow Dwarf Virus - Chiping Liu; Manwen Zhang; Chen Luo; Zuqing Hu (Agronomy)
Many plant viruses are transmitted by insect vectors, and the transmission process is regulated by key genes within the vector. However, few of these genes have been reported. Previous studies in our laboratory have shown that the expression of the signal transducer and activator of transcription 5B (STAT5B) in viruliferous vector aphids carrying barley yellow dwarf virus (BYDV) was upregulated, and the complement component 1 Q subcomponent binding protein (C1QBP) within the aphid interacted with the coat protein (CP) and aphid transmission protein (ATP) of BYDV. In this study, we examined the expression levels of STAT5B and C1QBP in the vector aphid Sitobion avenae (Fabricius) (Hemiptera: Aphididae) using the qPCR method. We conducted this analysis during the acquisition accession periods (AAPs) and inoculation accession periods (IAPs) of the BYDV species GAV (BYDV-GAV). Furthermore, the effects of STAT5B and C1QBP on the acquisition, retention, and transmission of BYDV-GAV in S. avenae were verified using the RNA interference (RNAi) method. The results show the following: (1) the expression levels of STAT5B and C1QBP were significantly upregulated during the AAPs and IAPs of BYDV-GAV; (2) the silencing of STAT5B led to a significant increase in BYDV-GAV retention during IAPs; and (3) the silencing of C1QBP resulted in a notable decrease in BYDV-GAV acquisition during the AAPs, as well as a significant increase in BYDV-GAV retention during the IAPs. These results suggest that STAT5B and C1QBP in S. avenae play a role in BYDV-GAV transmission. These findings highlight the functions of the STAT5B and C1QBP genes and identify C1QBP as a potential target gene for further RNAi-based studies to control the transmission of BYDV-GAV.